Eduard Schwartz und die Altertumswissenschaften seiner Zeit - Rebenich, Stefan (Hyperboreus, 2015)
Eduard Schwartz (1858–1940) represents the German tradition of Altertumswissenschaft which had a lasting inﬂuence on classical studies throughout the western world. His research is impressive both for its quantity and quality and conﬁrms the efﬁciency of the historico-critical method (Quellenforschung). Schwartz combined the editing and the interpretation of sources and accelerated the historicization of the ancient world. Philology, as Schwartz understood it, comprised historical scholarship which should take note of the entire spectrum of evidence from Greek and Roman antiquity. But Schwartz was also interested in the history of the early Church and edited, inter alia, Eusebius’ Historia ecclesiastica and the Acta Conciliorum Oecumenicorum. His editorial projects helped to shape the future of the discipline and remain indispensable for classical studies to this day. From a political point of view, Eduard Schwartz can be described as conservative. He advocated nationalist and antidemocratic positions and was openly hostile to the Weimar Republic, but did not support National Socialism. After 1933 he assisted some scholars who had to leave Germany on political or racial grounds.